Very Early Corona Treatment-Mediated Artificial Incubation of Silkworm Eggs and Germline Transformation of Diapause Silkworm Strains - Zhang, Yu-Li; Huang, Yang; Wang, Ping-Yang; Li, Qiang; Bi, Li-Hui; Zhao, Ai-Chun; Xiang, Zhong-Huai; Long, Ding-Pei (Frontiers in Bioengineering and Biotechnology, 2022)
Diapause is an important biological characteristic for many insect species to adapt to adverse environmental conditions and maintain the continuity of the race. Compared with the traditional hydrochloric acid or/and cold storage treatment methods, the artificial corona incubation technology of silkworm (Bombyx mori) eggs has many advantages including, the absence of pollution, easy operation and safety. However, this technology has not yet been applied in sericulture. In this study, we developed a novel artificial corona instrument to successfully disrupt the diapause of newly laid and refrigerated eggs from various Chinese and Japanese lineage silkworm strains. Subsequently, we invented a very early corona treatment (VECT) strategy to prevent the diapause of newly laid silkworm eggs within 4 h of oviposition. The hatching rates of the larvae were more than 95% in all diapause silkworm strains, which was comparable to the effect of the traditional HCl treatment strategy. In addition, we developed a combination strategy of VECT and pre-blastoderm microinjection and successfully created transgenic silkworms in various diapause strains. The results of the current study can aid in improving the corona artificial incubation technology and promote its application in sericulture.